Hypoxia-induced PD-L1 expression and modulation of muscle stem cell allograft rejection - Raiten, Jacob; Abd, Genevieve M.; Handelsman, Shane B.; Patel, Harshank V.; Ku, Jennifer C.; Parsons, Agata M.; Wassink, Jonathan L.; Hayes, Sheridan L.; Overbay, Juliana; Li, Yong (Frontiers in Pharmacology, 2024)
Stem cell therapy has shown immense promise in treating genetic disorders, particularly muscular diseases like Duchenne muscular dystrophy (DMD). This study investigates a novel method to enhance the viability of stem cell transplants in DMD by upregulating Programmed Death Ligand 1 (PD-L1) in muscle stem cells (MuSCs) through preconditioning with hypoxia and/or interferon-γ (IFN-γ) to mitigate T cell immune rejection. MuSCs were treated with 5% hypoxia for 72 h and further treated with IFN-γ to enhance PD-L1 expression. Additionally, gain and loss experiments using a PD-L1 inhibitor (BMS-1) were conducted to investigate cellular expression profiles in vitro and cell transplantation outcomes in vivo. Our results showed significant upregulation of PD-L1 in MuSCs under hypoxia and IFN-γ conditions without affecting cellular proliferation and differentiation in vitro. In vivo, these preconditioned MuSCs led to decreased infiltration of CD4+ and CD8+ T cells in implanted limb muscles of mouse models. Blocking PD-L1 reduced graft survival in muscles treated with MuSCs. Conversely, increased PD-L1 expression and reduced T cell infiltration correlated with improved graft survival, as identified by pre-labeled LacZ + MuSCs following transplantation. This study provides evidence that hypoxia and IFN-γ preconditioning of MuSCs can significantly enhance the efficacy of cell therapy for DMD by mitigating immune rejection. Our strategic approach aimed to improve donor cell survival and function post-transplantation by modifying immune responses towards the donor cells.